Jewish ideas of France
1 online resource.
Keywords: "This innovative exploration of various Jewish experiences in France and the Francophone world through nuanced questions and representations offers an intertwining of perspectives that challenge geographical, chronological, and theoretical boundaries. Engaging the transnational, it brings together studies highlighting the importance of migration, diaspora, identity, and empire for Jewish communities in metropolitan France and beyond. New and emerging scholars are invited into conversation with established thinkers to capture the present and future of French, Francophone, and Jewish Studies. Because identities are layered and multifaceted, the multidisciplinary studies in this volume are intended to illustrate how frameworks interact, overlap, and shift. The result of these efforts is a collection of essays that reveals the complex interplay between French and Jewish identities and how they have changed over time. Grounded in historical, literary, visual, sociological, and legal analyses, they delve into questions of gender, race, religion, empire, migration, culture, and communal life. Taken together, they problematize the categories often created to make meaning of complex dynamics. This book is an important secondary source for researchers, undergraduate and graduate students, and general readers interested in world history, Jewish Studies, French Studies, European Studies, and immigration and diaspora studies"-- Provided by publisher.